ANALISIS SPASIAL PERUBAHAN PENGGUNAAN LAHAN DI KABUPATEN PURBALINGGA - Lilian Anggraeni; Rita Noviani; Seno Budhi Ajar (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
The rapid development of the Purbalingga Regency region, supported by the establishment of increasingly complex regulations and significant population growth, has significantly impacted the demand for facilities and infrastructure development; this aims to realize development plans and meet the increasing needs of society. Changes in land use are an important factor that needs to be analyzed and planned carefully. This research aims to understand changes in land use in Purbalingga Regency. The method used involves interpreting Landsat images with predictive modeling of land use changes using Annual Neural Network and Cellular Automata (ANN-CA) to describe land use changes between 2009 and 2022 using data techniques observation. The research results show that the most dominant land uses in Purbalingga Regency include gardens, rice fields, forests, and settlements. The most striking change in land use is the transformation from forest and agricultural land to residential land. The residential land area 2009 was around 6,294.48 hectares, which increased significantly to around 15,183.88 hectares in 2022.